A retrospective case series on bisphosphonate related osteonecrosis of the jaw in 20 cats - Hatunen, Suzanna L.; Anderson, Jamie G.; Bell, Cynthia M.; Campos, Hugo C.; Finkelman, Matthew D.; Shope, Bonnie H. (Frontiers in Veterinary Science, 2024)
Introduction: This retrospective study highlights the salient aspects of a series of feline patients affected with bisphosphonate related osteonecrosis of the jaw. Though more commonly published in human literature, this presentation is rare in cats. The authors hope that this study will assist in making this a more globally known entity with subsequent improved prognosis. Methods: Data was retrospectively obtained from the medical records between 2015-2021 of twenty cats with Medication Related Osteonecrosis of the Jaw. Data included patient information, clinical history, presenting complaint, systemic diseases, details referable to hypercalcemia and treatment thereof, bisphosphonate specifics (dose and duration), clinical presentation of the lesion, diagnostic testing including radiographic and histopathologic descriptions, treatment, and outcome. Results: Pertinent results include that all twenty cats who developed Medication Related Osteonecrosis of the Jaw had been treated for idiopathic hypercalcemia with the bisphosphonate medication alendronate. Eighty-five percent of the cases had prior dental extractions at the site of MRONJ lesion. Ninety-five percent of the affected cats required a surgical procedure to control the disease. Thirty-five percent of cases required at least one revision surgery after the initial procedure was performed. Diagnosis of MRONJ was made by a correlation of diagnostic findings and patient history. No single diagnostic, or combination was pathognomonic for lesion diagnosis. As well, there were no statistically significant associations between patient variables assessed and the overall patient outcome.The case series reveals that cats with feline idiopathic hypercalcemia treated with alendronate may be at a risk for development of MRONJ, a serious oral condition with significant morbidity. Prior dental extraction sites in patients concurrently treated with bisphosphonate medications were often associated with MRONJ lesions. Therefore, any needed dental surgery should be performed prior to the use of bisphosphonates where possible. The authors have also included a relevant comparative literature review.